BEHIND PERFORMANCE : HOW WORK LIFE QUALITY AND WORKLOAD SHAPE JOB SATISFACTION? - Firdausi, Zahira; Setiani, Setiani (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This research aims to analyze the influence of quality of work life and workload on employee performance, with job satisfaction as a mediating variable at PT. X. The study employs a quantitative approach using a questionnaire distributed to employees of PT. X. The data collacted was analyzed using Partial Least Square Structural Equation Modelling (PLS-SEM). The results indicate that quality of work life has a positive and significant effect on job satisfaction and employee performance. Workload has a positive and significant effect on job satisfaction and employee performance. Futhermore, job satisfaction mediates the relantionship between workload an employee performance, and also mediates the relantionship between workload and employee performance. These finding provide valuable insights for PT. X in enchancing employee performance through improvements in quality of work life and effective workload management, recognizing the crucial mediating role of job satisfaction.